ChemInform Abstract: Synthesis of Orotidine by Intramolecular Nucleosidation. Issue 30 (July 2015) - Kim, E.‐K.; Krishnamurthy, R.
Abstract The approach for the synthesis of orotidine (III) is general and not limited to the ribofuranosyl skeleton.